2017
DOI: 10.7150/ijms.19021
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Nefopam Infusion during Laparascopic Cholecystectomy on Postoperative Pain

Abstract: Background: While recovery from remifentanil is fast due to its rapid metabolism, it can induce hyperalgesia by activation of N-methyl-D-aspartic acid (NMDA) receptors. Therefore, administration of NMDA receptor antagonists such as ketamine is effective in relieving hyperalgesia caused by remifentanil. A previous study showed that nefopam administration before anesthesia combined with low-dose remifentanil reduced pain and analgesic consumption during the immediate postoperative period. We hypothesized that in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…22 Nefopam is a non-opioid, non-steroidal benzoxazocinederived analgesic that inhibits monoamine reuptake in the central nervous system. 25,26 It indirectly modulates the NMDA receptor, inhibiting c-Fos expression in the dorsal horn of the spinal cord and relieving allodynia in rats. 11 Nefopam was first introduced as an antidepressant and anticonvulsant and was then reported to be efficacious in postsurgical hyperalgesia.…”
Section: Discussionmentioning
confidence: 99%
“…22 Nefopam is a non-opioid, non-steroidal benzoxazocinederived analgesic that inhibits monoamine reuptake in the central nervous system. 25,26 It indirectly modulates the NMDA receptor, inhibiting c-Fos expression in the dorsal horn of the spinal cord and relieving allodynia in rats. 11 Nefopam was first introduced as an antidepressant and anticonvulsant and was then reported to be efficacious in postsurgical hyperalgesia.…”
Section: Discussionmentioning
confidence: 99%
“…Dexmedetomidine, a selective α 2 ‐adrenergic agonist, also reduced opioid‐induced hyperalgesia in rats (Yuan et al., ; Zheng et al., ) and humans (Lee, Kim, & Kim, ) by potentiating noradrenergic inhibition in the spinal cord. Nefopam, a monoamine reuptake inhibitor, successfully opposed the hyperalgesic effects of opioids in humans (Choi et al., ; Kim et al., ). These results suggest the clinical interest of using drugs that modulate the activity of NMDA receptors and monoamine system to disrupt sensitization processes underlying pain hypersensitivity, and consequently restoring the analgesic efficacy of opioid agonists under neuropathic pain conditions.…”
Section: Neuropathological Mechanisms Shared By Neuropathic Pain and mentioning
confidence: 99%
“…Intravenous administered Nefopam determines a strong inhibition of the nociceptive flexion reflex in humans [21]. Studies has shown that it has opioid-sparing effects (it reduces de opioid consumption after cholecystectomy [22], cardiac surgery [11], upper and lower abdominal surgery [23,24], hysterectomy [25], palliative interventions [26,27], breast cancer surgery [28], nasal surgery, orthopedic interventions [29,30], by 30-40% [2] and that 20 mg of Nefopam is equipotent with almost 6-12 mg Morphine and 50 mg of Meperidine [31] having the same analgesic potency as nonsteroidal anti-inflammatory drugs.…”
Section: Pharmacological Propertiesmentioning
confidence: 99%